Study on methane hydrate distributions in laboratory samples by electrical resistance characteristics during hydrate formation - He, Juan; Li, Xiaosen; Chen, Zhaoyang; Li, Qingping; Zhang, Yu; Wang, Yi; You, Changyu (Journal of Natural Gas Science and Engineering, 2020)
To determine hydrate distributions in laboratory samples, a 5.701 L cylindrical reactor was designed and fabricated to synthesize hydrate-bearing samples with the excess-water method. The influences of temperature, water content, gas content, and electrode distance on the changing rules of electrical resistance, as well as measuring electrical resistance in nine samples, were systematically studied. The results indicated that the electrical resistance was increased with decreasing temperature, reducing water content or increasing gas content in deionized water settings, resembling electrical resistance changes in brine system. These rules were further used to analyze electrical resistance characteristics in the whole process of preparing and forming hydrate-bearing samples. Fresh hydrate formation was found to govern the electrical resistance increases after the induction periods. Resistance ratio and net increase of resistance analyses showed that the hydrate distributions in the samples with small hydrate saturations suffered more heterogeneity. Hydrate distributions in the samples with small and large hydrate saturations were inferred to be mass-like and rod-like, respectively. In addition, the dissociation of a sample (S-h = 19.46%) by depressurization confirmed more hydrates were dispersed near the right side of this cylindrical sample, which was in agreement with the result from electrical resistance analysis. Since hydrate distributions affected the outcomes of physical simulations, this work may offer some references to similar studies.